On some properties of bundles of trajectories of a controlled bilinear inclusion - Komleva, T. A.; Plotnikov, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We consider a differential bilinear inclusion with control and present conditions under which the reachability set for this inclusion is compact.